Develop concept and perform design verification to enchance FMS slip-on-lock connectors(20") to be Annex F PR 2 qualified - Lai, Gary Zhen Guang (2014)
The slip-on-lock connector is a bottom end connection for a casing head spool and it serves as a quick means for attachment to the conductor casing. The conductor casing prevents the collapse of the drilled hole, and also provides support for the entire weight of the wellhead and the Christmas tree. The slip-on-lock connector is a FMC proprietary design. The stress analysis and loading limitations of the 20 inch slip-on-lock connection when subjected to complex loadings was investigated using finite element analysis. The regions of high stress concentrations and deformations were identified. The computational results show that yielding had occurred on the bolting of the connector, which was caused by tensile stress effects arising from the combined loading. An improved design was proposed to fulfill the API 6A Annex F PR 2 requirements. The computational results were compared with available analytical solutions and were found to be in close agreement. Parametric variation of the geometry of the bolting and its arrangement was carried out, so as to develop a better design that improves the loading capabilities of the slip-on-lock connection.